IMPLEMENTASI KEBIJAKAN KREDIT USAHA RAKYAT DI BANK RAKYAT INDONESIA UNIT BAHU MANADO - GOBEL, MUHAMAD (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : Micro business, small and medium enterprises (UMKM) have the role and an important contribution ini Indonesian economy, namely to providing employment opportunities broad and contributed significant on the establishment of gross domestic product. Since disbursed policy/KUR program, People’s Bank of Indonesia (BRI) appointed as one of the executing banks. One KUR wich carried out by of BRI is KUR micro. This research purpose to find of policy loans for small-scale businesses (KUR) micro in BRI unit Bahu. The theory used in this writing is the implementation of public developed by George R. Edward III who pointed four variable that are important in the achievements of the success of the implementation of a policy: communication, resources, disposition and bureaucratic structure. The method of research is the method descriptive-qualitative. The results of the study showed that there is good communication, the availability of human resources employees who adequate in quality and quantity of and resources sufficient financial, the level of disposition or commitment and consistency civil servant and employee who high, and the structure of bureaucracy/implementing organizations (SOP and the distribution of duty and responsibility) eho obviously and flatly, so that the policy/micro KUR program was running properly and successfully consistent with the objectives, the objective and outcomes that has been set. This research is expected to give a valuable contribution in the development of the theory of public policy which was about the concept of the implementation of public policy and give feedback to the government and BRI that can be used ase one ingredient information and materials consideration in order to improve the effective implementation of the policy the people business credit (KUR) micro.Keywords: UMKM, KUR, BRI, Bahu